Caregiver strain in spouses of stroke patients - Blake, Holly (2001)
The aim of this thesis was to identify both patient and carer factors relating to caregiver strain in spouses of stroke patients. The secondary aim was also to assess the effectiveness of an intervention in reducing levels of strain, involving the provision of cognitive assessment information to both patients and spouses.